2018
DOI: 10.18203/2394-6040.ijcmph20181684
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of school based educational intervention for healthy body mass index and its association with academic performance among school children: a quasi-experimental study

Abstract: Background: Childhood obesity is associated with a higher chance of premature death and disability in adulthood, according to the World Health Organization. More than two-thirds of the adolescents aged 11-17 years are physically inactive in India as per WHO standards. Hence, school based Healthy life style curriculum development is the need of the hour for school children. The objectives of the study were to promote healthy lifestyle, by implementing school based intervention program (physical activity and nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Similarly, it has been found that the time of physical exercise at healthy intensity levels is far from the recommendations in extracurricular sports activities for children (Moral, 2018). While it has been shown that adapted sports programs in school children improve parameters related to healthy body composition (Manjula et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been found that the time of physical exercise at healthy intensity levels is far from the recommendations in extracurricular sports activities for children (Moral, 2018). While it has been shown that adapted sports programs in school children improve parameters related to healthy body composition (Manjula et al, 2018).…”
Section: Introductionmentioning
confidence: 99%